2018
DOI: 10.1155/2018/4965193
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Associated Socioeconomic Determinants in Rural and Urban Tanzania: Results from the 2012 WHO-STEPS Survey

Abstract: Background. Physical inactivity contributes to the rising prevalence of noncommunicable diseases (NCDs). Given the rapidly increasing prevalence of NCDs in Low-Income Countries (LICs), comprehensive evaluation and documentation of physical activity (PA) status in this setting are crucial. Methods. We examined the demographic and social-economic antecedents of PA among adults (5398) from the 2012 Tanzania STEPS survey data. Statistical significance at the level of 0.05 was used to measure the strength of associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
2
13
3
Order By: Relevance
“…Nearly 90% of participants in this study were categorized as being inactive or underactive. Contrary to our findings, earlier local studies revealed physical activity rates between 83.2% [16] to 92.6% [44]. Such discrepancy could partly be explained by the variation in the assessment tools used to assess for physical activity among studies, however, based on the observed obesity rates such rates are likely to be a true reflection.…”
Section: Discussioncontrasting
confidence: 99%
“…Nearly 90% of participants in this study were categorized as being inactive or underactive. Contrary to our findings, earlier local studies revealed physical activity rates between 83.2% [16] to 92.6% [44]. Such discrepancy could partly be explained by the variation in the assessment tools used to assess for physical activity among studies, however, based on the observed obesity rates such rates are likely to be a true reflection.…”
Section: Discussioncontrasting
confidence: 99%
“…Nearly 90% of participants in this study were categorized as being inactive or underactive. Contrary to our findings, earlier local studies revealed physical activity rates between 83.2% 16 to 92.6% 40 . Such discrepancy could partly be explained by the variation in the assessment tools used to assess for physical activity among studies, however, based on the observed obesity rates such rates are likely to be a true reflection.…”
Section: Discussioncontrasting
confidence: 99%
“…We also recorded family history of diabetes (Yes/No[referent]). Behavioral risks included alcohol consumption (current/past vs never[referent]) 37 , smoking (current/past [referent] vs never), fruits/vegetables (<5 days/week [referent] vs ≥5 days/week), 34 cooking with oil (vegetable oil [referent] vs non-vegetable oil), physical activity (low <600 MET/week vs high [≥600 MET/week, referent]) 38 and meals eaten outside the home/per week (3–7 meals/week [referent] vs 8–28 meals/week).…”
Section: Methodsmentioning
confidence: 99%